Vitamins C and E alleviate the deleterious effects of electronic cigarettes on tongue muscles and nerves in rat model - Yasmine M. Tolba; Raghda A. Abou ayana; Dina A. Nagui (BMC Oral Health)
Abstract Background This study evaluated the ultrastructural effects of electronic cigarettes’ (EC) exposure in rat lingual nerves and muscles and assessed the therapeutic roles of vitamins C, E, and their combination. Methods Forty adult male albino rats were allocated into 5 groups. Control: injected saline intraperitoneally, EC group: injected EC-liquid containing nicotine at a dose of 0.75 mg/kg, EC + C group: injected with EC-liquid and then supplemented orally with vitamin C, EC + C group injected with EC-liquid and then supplemented orally with vitamin E, and EC + C&E group: injected with EC-liquid and then supplemented orally with a combination of both vitamins. Transmission electron microscopy (TEM) and oxidative stress biomarkers malondialdehyde (MDA), and superoxide dismutase (SOD) were used to assess tissue damage and antioxidant effects. Results EC group showed disrupted myelin sheaths, abnormal mitochondria, elevated MDA, and reduced SOD activity, indicating oxidative damage. EC + C group showed muscular recovery but did not significantly improve oxidative markers (p > 0.05) when compared to EC group. EC + E and EC + C&E groups showed regular myelin sheaths, normal mitochondria, and significant improvements in MDA and SOD levels compared to the EC group (p < 0.01). Conclusions Vitamin E alone or combined with vitamin C effectively mitigates EC-induced oxidative stress and ultrastructural damage in muscular and nerve tissues. Vitamin C alone offers insufficient protection, mostly supporting muscular recovery without significantly improving nerve integrity or oxidative status.